Exploring the strategies of education leaders in managing under-achieving faculty - Bedaria I. Amerol; Erwin B. Berry; Jason V. Chavez; Analiza B. Calles; Michael Angelo A. Legarde; Shella S. Gador; Lergie L. Emologa; Analiza D. Camarista (Environment and Social Psychology, 2025)
Managing under-achieving faculty remains a major challenge in Philippine higher education, where tenure protections, cultural norms, and institutional diversity complicate accountability. This study explored the strategies of 18 academic leaders, from state universities in Lanao del Sur, Zamboanga Peninsula, Iloilo, and Palawan, through semi-structured interviews analyzed with reflexive thematic analysis. Findings show that leaders employ a stepwise approach: starting with coaching, mentoring, and reflective conversations, and escalating to improvement plans or disciplinary measures when necessary. Faculty responsiveness, institutional culture, and collaboration with stakeholders shaped outcomes. Leaders balanced empathy with accountability while facing structural barriers such as ambiguous policies, tenure protections, and cultural reluctance toward confrontation. Emotional and time-intensive demands further underscored the complexity of managing underperformance. The study highlights that effective management combines developmental support with accountability and must be adapted to institutional and cultural contexts. Limitations include reliance on leaders’ self-reports, exclusion of faculty and student perspectives, and cultural specificity, which may restrict generalizability. Future research should employ comparative and mixed-methods designs to test these themes across contexts and examine their long-term impact.